The Structural Hydrogeological Analysis of Formation of Underground Waters - Pozilov M.N.; Qurbanova L.M; Ibrohimova Z.I (Genius Journals, 2022)
In the clause the structural hydrogeological analysis of formation of underground waters is given.
Keywords: Groundwater; , water exchange, tectonic faults, groundwater; regime, hydrodynamic and hydrochemical regime, formation,